A4_1 War of the Worlds - Winkworth, David; Tudor, Vlad; Shaw, Elliott (Physics Special Topics, 2012)
H.G. Wells popular novel ‘The War of the Worlds’ involved the invasion of Earth by Martians who arrived via cylinders fired from enormous space guns mounted on Mars. This report explores the logistics of such artillery based on the technology of the time. By calculating the required escape velocity of Mars and considering the mass of the cylinders, an estimate of the necessary gunpowder is found to be over 120 tonnes. The resulting acceleration is then explored and found to be upwards of 100g. It is hypothesised that, whilst this would prove fatal to humans, Martians may be able to survive and so Wells theory is not entirely without merit.